Roars, groans and moans: Anatomical correlates of vocal diversity in polygynous deer. Issue 6 (3rd August 2021) - Frey, Roland; Wyman, Megan Tompkins; Johnston, Malcolm; Schofield, Michael; Locatelli, Yann; Reby, David
Abstract: Eurasian deer are characterized by the extraordinary diversity of their vocal repertoires. Male sexual calls range from roars with relatively low fundamental frequency (hereafter f o ) in red deer Cervus elaphus, to moans with extremely high f o in sika deer Cervus nippon, and almost infrasonic groans with exceptionally low f o in fallow deer Dama dama . Moreover, while both red and fallow males are capable of lowering their formant frequencies during their calls, sika males appear to lack this ability. Female contact calls are also characterized by relatively less pronounced, yet strong interspecific differences. The aim of this study is to examine the anatomical bases of these inter‐specific and inter‐sexual differences by identifying if the acoustic variation is reflected in corresponding anatomical variation. To do this, we investigated the vocal anatomy of male and female specimens of each of these three species. Across species and sexes, we find that the observed acoustic variability is indeed related to expected corresponding anatomical differences, based on the source‐filter theory of vocal production. At the source level, low f o is associated with larger vocal folds, whereas high f o is associated with smaller vocal folds: sika deer have the smallest vocal folds and male fallow deer the largest. Red and sika deer vocal folds do not appear to be sexually dimorphic, while fallow deer exhibit strong sexual dimorphism (after correcting for body size differences). At the filter level, the variability in formants is related to the configuration of the vocal tract: in fallow and red deer, both sexes have evolved a permanently descended larynx (with a resting position of the larynx much lower in males than in females). Both sexes also have the potential for momentary, call‐synchronous vocal tract elongation, again more pronounced in males than in females. In contrast, the resting position of the larynx is high in both sexes of sika deer and the potential for further active vocal tract elongation is virtually absent in both sexes. Anatomical evidence suggests an evolutionary reversal in larynx position within sika deer, that is, a secondary larynx ascent. Together, our observations confirm that the observed diversity of vocal behaviour in polygynous deer is supported by strong anatomical differences, highlighting the importance of anatomical specializations in shaping mammalian vocal repertoires. Sexual selection is discussed as a potential evolutionary driver of the observed vocal diversity and sexual dimorphisms. Abstract : The comparison of three species of acoustically diverse polygynous deer suggests that acoustic variability is related to corresponding anatomical differences of the vocal organs.